2007
DOI: 10.1523/jneurosci.2001-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Astrocytic Ca2+Signals Contribute to Neuronal Excitotoxicity after Status Epilepticus

Abstract: Status epilepticus (SE), an unremitting seizure, is known to cause a variety of traumatic responses including delayed neuronal death and later cognitive decline. Although excitotoxicity has been implicated in this delayed process, the cellular mechanisms are unclear. Because our previous brain slice studies have shown that chemically induced epileptiform activity can lead to elevated astrocytic Ca 2ϩ signaling and because these signals are able to induce the release of the excitotoxic transmitter glutamate fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
264
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(283 citation statements)
references
References 48 publications
(82 reference statements)
18
264
1
Order By: Relevance
“…Presumably because of their proximity to blood vessels, our data indicate that tail-vein loading of TMRM preferentially labels astrocyte mitochondria. We demonstrated that TMRM-stained peri-nuclear mitochondria colocalize with cells that can be labeled with the astrocyte-specific dye sulforhodamine 101 (SR101) 15 as shown in Figures 4D and 4F. To correct for spectral overlap in Figures 4D and 4F, the TMRM image at 6 hours was subtracted from the SR101 plus TMRM image at 7 hours after RB photothrombosis.…”
Section: Stroke Induction By Rose Bengal Photothrombosis and Drug Admmentioning
confidence: 94%
See 1 more Smart Citation
“…Presumably because of their proximity to blood vessels, our data indicate that tail-vein loading of TMRM preferentially labels astrocyte mitochondria. We demonstrated that TMRM-stained peri-nuclear mitochondria colocalize with cells that can be labeled with the astrocyte-specific dye sulforhodamine 101 (SR101) 15 as shown in Figures 4D and 4F. To correct for spectral overlap in Figures 4D and 4F, the TMRM image at 6 hours was subtracted from the SR101 plus TMRM image at 7 hours after RB photothrombosis.…”
Section: Stroke Induction By Rose Bengal Photothrombosis and Drug Admmentioning
confidence: 94%
“…The cortical loading of Fluo4-AM is highly specific for astrocyte labeling in vivo. 15 For mitochondrial membrane potential imaging, potential sensitive dye tetramethyl rhodamine methyl ester (TMRM) was dissolved in DMSO, diluted in sterilized PBS (100 mM) and tail-vein injected. Tetra-methyl rhodamine methyl ester is a lipophilic cation indicator that equilibrates across membranes in a Nernstian fashion.…”
Section: Stroke Induction By Rose Bengal Photothrombosis and Drug Admmentioning
confidence: 99%
“…In general, these observations suggest that widespread intercellular calcium waves are not likely to occur between astrocytes under physiological conditions in situ. However, a recent in vivo study showed that "Ca 2+ signals (…) can propagate through the cell and couple to adjacent astrocytes in the form of a Ca 2+ wave" (Ding et al;. These changes in [Ca 2+ ] i can act as a second messenger in various cellular process, including the release of gliotransmitters or the modification of gene expression patterns.…”
Section: Calcium Signaling In Astrocytesmentioning
confidence: 99%
“…Later studies demonstrated that this process can be observed in acute brain slices[71,72,73,74,75,76,77,78,79] and in vivo [80]. Astrocytes were later shown to release a number of chemical transmitters, including ATP[81,82,83,84,85], D-serine[86,87,88,89], TNF-alpha[90,91], and ANP[92], in a process that has recently been termed gliotransmission[93].…”
Section: Astrocytes As Neuromodulatorsmentioning
confidence: 99%